A purposive approach to labour law - Davidov, Guy (Oxford, 2016)
"The mismatch between goals and means is a major cause of crisis in labour law. The regulations that we use - the legal instruments and techniques - are no longer in sync with the goals they are supposed to advance. This mismatch leads to a problem of coverage, where many workers who need the protection of labour law are not covered by it, as well as a problem of obsoleteness, as labour laws are not sufficiently updated in light of dramatic changes in the labour market.